Tetranuclear Copper(II) Complexes with Simultaneous Phenoxo and Azido Bridges ‐ Synthesis, Structural and Magnetic Studies. Issue 37 (1st October 2018) - Pandey, Priyanka; Dwivedi, Nidhi; Cosquer, Goulven; Yamashita, Masahiro; Sunkari, Sailaja
Abstract: Tetradentate Schiff base ligands with multiple coordinaton sites are one of the best choice for the construction of multinuclear metal complexes. Coupled with auxiliary ligands under self assembling conditions, the scope for generating new structures increases manifold due to various structure directing factors in operation. Though, phenoxo or azido bridged copper(II) systems have been investigated thoroughly from structural and magnetic aspects, the literature is scanty with combined phenoxo and azido bridged systems. In a study on the effect of synthetic conditions on the structures generated and associated magnetic properties, two new tetranuclear copper complexes, viz., [Cu4 (L1)2 (μ‐N3 )2 (N3 )2 ] (1 ) and [Cu4 (L2)2 (μ‐N3 )2 (N3 )2 ] (2 ) where L1=N, N′‐Bis(salicylidene)diaminopropane (salpn) and L2=N, N′‐Bis(salicylidene)diaminobenzene (salophen) with both phenoxo and azido bridges are reported. The tetranuclear cluster is made of two inversion related dimers built of phenoxo bridged Cu1 and Cu2 with distorted square planar and square pyramidal geometries respectively. These dimers are bridged by symmetrically bridging azides leading to a tetranuclear core. The contrasting magnetic behavior inspite of same coordination environments, antiferromagnetic in1 (J1 =−2.17 cm −1 ; J2 =−28.15 cm −1 ) and ferromagnetic in2 (J1 =−74.7 cm −1 ; J2 =146.5 cm −1 ), is understood in terms of lower bridge angles and closer separation between copper centers in2 than in1 . Abstract : Multinuclear Cu II systems involving both phenoxo and azido bridges are scarce in literature, though there are several examples of multinuclear Cu II systems with individual phenoxo or azido bridges. As structurally diverse systems can be stabilised by modifications in the synthetic conditions, our attempts with Cu II, azide and different amine based schiff bases viz., salpn/salophen have resulted in title complexes whose structural and magnetic studies are presented here. Though the core structure of both the complexes is same, they exhibit totally contrasting magnetic behaviour, antiferromagnetic in1 (J1=‐2.17 cm −1 ; J2=‐28.15 cm −1 ) and ferromagnetic in 2 (J1=‐74.7 cm −1 ; J2=146.5 cm −1 ). Such a contrasting behaviour is understood in terms of lower bridge angles and closer separation between copper centers in2 than in1 . As synthetic conditions play a decisive role in stabilizing structures, there is plenty of scope for generating desired structures by carefully controlling the variables and looking into their magnetic behavior, thus leading to structurally rich and magnetically versatile systems.